1993
DOI: 10.1002/ijc.2910540404
|View full text |Cite
|
Sign up to set email alerts
|

trk and ret proto‐oncogene expression in human neuroblastoma specimens: High frequency of trk expression in non‐advanced stages

Abstract: Forty-three fresh tumor specimens of human neuroblastoma belonging to different clinical stages were analyzed for the expression of 2 proto-oncogenes: trk, which encodes a tyrosine-kinase receptor for nerve growth factor (NGF) and ret, another receptor-type tyrosine kinase whose ligand is unknown. The mRNA expression of the trk gene was detected in 67.4% of cases, with increased frequency in I, II and IVs Evans' stages and in patients with favorable prognosis according to the Shimada classification. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…Combining our own present and previous results (Kogner et al, 1993) with those from other groups (Borello et al, 1993;Kaplan et al, 1993;Matsumoto et al, 1995;Nakagawara et al, 1994;Suzuki et al, 1993) a specific pattern of neurotrophin receptor expression in various neuroblastoma tumours emerges. Favourable neuroblastoma tumours express trkA together with p75LNGFR and sometimes full-length trkC, but only truncated trkB.…”
supporting
confidence: 86%
“…Combining our own present and previous results (Kogner et al, 1993) with those from other groups (Borello et al, 1993;Kaplan et al, 1993;Matsumoto et al, 1995;Nakagawara et al, 1994;Suzuki et al, 1993) a specific pattern of neurotrophin receptor expression in various neuroblastoma tumours emerges. Favourable neuroblastoma tumours express trkA together with p75LNGFR and sometimes full-length trkC, but only truncated trkB.…”
supporting
confidence: 86%
“…As mentioned above, although Ret has been consistently found expressed in neuroblastoma tumor specimens and in most neuroblastoma-derived cell lines, no clear evidence has been reported that may support its involvement in neuroblastoma pathogenesis, and its expression does not correlate with disease aggressiveness (10,11). On the other hand, in primary cultures, GDNF and neurturin cooperate with RA to induce neurite outgrowth and GDNF induces neuronal differentiation in lowgrade but not in high-grade neuroblastoma cells (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Several characteristics have been identified that predict the outcome of NB patients. In patients with a good prognosis, tumors occur in infants (o1 year), are aneuploid, lack loss of heterozygosity (LOH) at 1p or N-myc amplification and express relatively high levels of TrkA mRNA (Borello et al, 1993;Kogner et al, 1993;Nakagawara et al, 1993;Suzuki et al, 1993). Indicators of poor prognosis include clinical presentation in older children (41 year) of tumors that are diploid, contain LOH at lp and amplification of the N-myc proto-oncogene.…”
Section: Introductionmentioning
confidence: 99%